Effect of nanoporosity on the electromagnetic wave absorption performance in a biomass-templated Fe3O4/C composite: a small-angle neutron scattering study. Issue 1 (4th December 2019) - Fang, Yuan; Xue, Weidong; Zhao, Rui; Bao, Shengxiang; Wang, Wenjian; Sun, Liangwei; Chen, Liang; Sun, Guangai; Chen, Bo
Abstract : Small-angle neutron scattering was used to investigate the effect of nanoporosity on electromagnetic wave absorption in biomass-templated Fe3 O4 /C. Abstract : A hierarchically porous Fe3 O4 /C composite was synthesized with a biomass-templated carbothermal strategy and tested as an electromagnetic (EM) wave absorber. The hollow fibrous structure of the cotton template was well retained in the product. The sample synthesized at 600 °C exhibited a wide effective absorption bandwidth of 4.4 GHz at a small thickness of 2.0 mm. Nitrogen sorption and small-angle neutron scattering revealed the evolution of a nanoporous structure as the synthesis temperature increased, based on which a correlation between nanoporosity and EM wave absorption performance was established. This study illustrated that porosity should be kept at a moderate level for highly efficient EM wave absorption.